Association of combinations of interleukin-10 and pro-inflammatory cytokine gene polymorphisms with dengue hemorrhagic fever. Issue 1 (July 2015) - Alagarasu, K.; Bachal, R.V.; Tillu, H.; Mulay, A.P.; Kakade, M.B.; Shah, P.S.; Cecilia, D.
Highlights SNPs in TNF, IFNG, IL1B, IL8, IL0, IL17A and IL17F genes were investigated in 132 dengue cases and 108 healthy controls. IL8 rs4973 A/T and IL10 rs1800871 A/G genotypes were negatively associated with dengue hemorrhagic fever (DHF). Combinations of IL10 rs1800871 and pro-inflammatory cytokine genotypes influence the risk of DHF.